CRP/albumin ratio and WBC values correlate with Ki-67 and survival in glioblastoma multiforme - Güven Gürsoy (Frontiers in Oncology)
IntroductionGlioblastoma multiforme (GBM) is an aggressive central nervous system tumor that results in poor overall survival due to its rapid and aggressive course. Prognostic indicators are important in treatment strategies. This study aimed to investigate the effectiveness of inflammatory markers C-reactive protein (CRP)/albumin ratio, and white blood cell (WBC) count, as well as the pathological indicator Ki-67, for survival prediction and prognosis and their superiority.Material and methodsThe demographic data of the patients, Glasgow Coma Scale (GCS), WBC, CRP, albumin, CRP/albumin values, Ki-67 values ​​at pathological diagnosis, and overall survival were examined in this study. Adults over the age of 18 who underwent gross total surgery in a single center and whose pathological diagnosis was glioblastoma multiforme, who received radiotherapy and chemotherapy after surgery, were included. Patients with chronic and comorbid diseases were excluded because of their potential to affect the parameters to be examined.ResultsAmong the 133 GBM cases, between 23 and 72 years of age were included, and 72.9% (n: 97) had a survival less than one year survival. Ki-67, WBC, CRP, albumin, and the CRP/albumin ratios were found to be statistically significant for 1-year overall survival (p values ​​in order: <0.001, <0.001, <0.001, 0.013, <0.001). The receiver operating characteristic (ROC) curve analysis revealed significant cutoff value at 22.5 for Ki-67, 0.70 for CRP/albumin ratio, and 7.42 for the WBC count for 1-year survival.ConclusionThe WBC count, CRP/albumin ratio, and Ki-67 parameters can be used to predict 1-year overall survival in patients with glioblastoma multiforme. These findings emphasize the need for more prognostic scoring models and evaluations of the role of inflammation in GBM prognosis.